HUBUNGAN ANTARA WORKPLACE BULLYING TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT. TIGA MANUNGGAL TEXTILE (TIMATEX) SALATIGA - Giovannny Permata Putri; Sutarto Wijono (Jurnal Psikologi TALENTA, 2018)
The purpose of this research was to describe examine the correlation between workplace bullying with employee work procuctivity at PT. Tiga Manunggal Textile (Timatex) Salatiga. The subject of this research is too employees of the Timatex company in seazing and weaving divisions. This result shows r = -0,312 and p = 0,002indicate that there is a negative and significant correlation betwen two variables.